340 c-Met/β1 Integrin: A Receptor Complex Driving Invasive Glioblastoma Resistance to Antiangiogenic Therapy. (1st August 2016) - Sidorov, Maxim; Jahangiri, Arman; Han, Sung-Won; De Lay, Michael; Wagner, Jeffrey; Castro, Brandyn; Flanigan, Patrick Michael; Imber, Brandon S.; Weiss, William A.; Aghi, Manish Kumar
Abstract: INTRODUCTION: Invasive resistance limits antiangiogenic therapy for glioblastoma. We previously reported upregulated c-Met and β1 integrin in bevacizumab-resistant glioblastomas. We hypothesized that chemotactic c-Met and haptotactic β1-integrin interact in resistant tumors. METHODS: We utilized immunoprecipitation, proximity ligation assays (PLAs), cell-culture biological assays, general cloning, and immunohistochemistry. RESULTS: Immunoprecipitated lysates of intracranial U87-BevR and U87-BevS xenografts, isogeneic models of bevacizumab resistance and responsiveness, revealed robust physical c-Met/β1-integrin interactions in bevacizumab-treated U87-BevR, and minimal c-Met/β1-integrin complex in IgG-treated U87-BevR or IgG/bevacizumab-treated U87-BevS. PLAs mirrored immunoprecipitation results. In culture, complex formation increased dose-dependently by bevacizumab, c-Met ligand HGF, and hypoxia. VEGF165 and endothelial cell-conditioned medium inhibited complex formation. Using far-Western blotting, we found that only the extracellular c-Met domain bound β1-integrin. This c-Met/β1-integrin interaction led to cross-activation, with increasing concentrations of β1-integrin ligand fibronectin increasing ligand-independent c-Met phosphorylation. This activation was inhibited with integrin-linked kinase knockdown. Inducing the complex through the iDimerize system, in which we tagged β1-integrin and c-Met with complementary proteins binding on heterodimer addition, increased migration ( P < .05). Site-directed biopsy in a bevacizumab-resistant glioblastoma patient revealed increased complex formation progressing from core to enhancing edge to invasive cells outside enhancement. PLAs revealed 20-fold more c-Met/β1 complexes after bevacizumab resistance in patient specimens compared with a 2-fold increase in bevacizumab-naive glioblastomas at recurrence ( P < .05). Furthermore, the percentage of β1-integrin bound to c-Met in 20 patient glioblastomas at diagnosis correlated inversely with survival ( P < .05). Treating xenografts with 3 mg/kg bevacizumab was as effective as 10 mg/kg; however, only the latter contained c-Met/β1 complexes. Similarly, a patient receiving low-dose bevacizumab demonstrated negligible complex by PLA. CONCLUSION: β1-integrin forms a complex with c-Met in bevacizumab-resistant glioblastoma leading to allosteric cross-activation driving invasive resistance. Complex formation at high but not low antiangiogenic therapy doses despite equal efficacy suggests that, for anti-angiogenic therapy, "less is more."